UCD model in agile software processes - Butt, Saad Masood; Anatolyevna, Gnevasheva Vera; Salmani, Hosna (International Journal of Advances in Applied Sciences, 2021)
Software development field is becoming more productive day by day with the wonderful model name Agile. Agile is the main focus of research now a days. It is because of its abilities of handling changes in efficient way through iterative and incremental practices. Although it became famous because of its capabilities still there are some issues in it, which is ignorance of usability engineering in different phases of agile that is an important aspect to understand the software. Usability has deep roots in software quality and is a core construct of HCI. To develop interactive and usable systems there is a need of such a model which can integrate HCI with Agile. To address this issue. To solve this issue we have proposed a model which will work with both User Centered (main focus of HCI) and Agile by assembling different practices from both fields which will result useable products. It will enhance software life with user satisfaction by giving them running software with usability.